Detection of Sectoral Modes in the Eclipsing Binary KIC 4851217. Issue Volume 14:Issue S339(2018) (November 2017) - Fedurco, M.; Parimucha, Š.; Gajdoš, P.
Abstract: KIC 4851217 is a short period eclipsing binary ( P = 2.47 days) in the field of the Kepler K1 mission. As well as variability caused by the eclipses, low-amplitude pulsations are also present in the data. A frequency analysis of the residual light-curve revealed δ Sct pulsations in the frequency range from 15–21 d −1 with amplitudes up to 3.5 mmag. Strong linear coupling ( fi = fp + kforb ) to orbital frequency was found, indicating tidally locked modes. From an analysis of 5 selected groups of frequencies we identified a radial mode on the secondary component, 3 dipole modes ( l = |m| = 1), one of them present on the secondary component, and a quadrupole mode ( l = |m| = 2), also located on the secondary component.